Clinical and functional features of dilated cardiomyopathy in cancer patients after covid-19 infection (Bangladesh Journal of Medical Science, 2026)
Background Dilated cardiomyopathy (DCM) remains one of the leading causes of chronic heart failure worldwide. The COVID-19 pandemic has significantly changed the clinical landscape of cardiovascular diseases, revealing new mechanisms of myocardial injury. Patients with cancer represent a particularly vulnerable group due to cardiotoxic anticancer therapies and immune dysfunction. The combined impact of oncological disease, cardiotoxic treatment and SARS-CoV-2 infection may lead to rapid progression of heart failure and unfavorable outcomes. Aim To analyze clinical and functional features of dilated cardiomyopathy in patients with oncological diseases after COVID-19 infection. Materials and Methods A narrative literature review and clinical case analysis were performed. Contemporary studies on post-COVID cardiovascular complications, inflammatory cardiomyopathy and cardio-oncology were analyzed. Particular attention was paid to mechanisms of myocardial injury and progression of heart failure in cancer patients after SARS-CoV-2 infection. Results Recent evidence demonstrates that SARS-CoV-2 has a pronounced tropism for cardiomyocytes and vascular endothelium via ACE2 receptors. The main mechanisms of myocardial injury include direct viral cytotoxicity, cytokine storm, endothelial dysfunction, microvascular thrombosis and autoimmune inflammation. Long-term follow-up studies show a significantly increased risk of heart failure, arrhythmias and dilated cardiomyopathy after COVID-19. Cancer patients represent a high-risk population due to cardiotoxic chemotherapy, immune checkpoint inhibitors and radiation therapy. The risk of heart failure after COVID-19 in oncology patients increases by 2–3 times, while thromboembolic complications occur several times more frequently. The presented clinical case illustrates rapid progression of heart failure and fatal outcome in a patient with DCM after COVID-19 infection, consistent with the phenotype of post-COVID inflammatory cardiomyopathy. Conclusion SARS-CoV-2 infection should be considered an independent trigger of dilated cardiomyopathy progression. Cancer patients represent an extremely high-risk group due to synergistic myocardial injury caused by cardiotoxic therapy and post-COVID inflammatory mechanisms. Early cardiovascular risk stratification and multidisciplinary management are essential to improve outcomes in this patient population.BJMS, Vol. 25 No. 02 April’26 Page: 633-638